(untitled) (Medical Forum Monthly, 2024)
Objective: The objective of the study was to evaluate the frequency and risk factors for CSOMWC in children of IDPs of North Waziristan Agency during military operation “ZARB-E-AZAB” started in July 2014. Study Design: Observational study / cross sectional Place and Duration of Study: This study was conducted at the ENT Department, DHQ hospital Bannu and two main clinics serving major populations of the IDPs from 3rd December 2014 to 5th May 2015. Materials and Methods: Data was recorded during the child's visit to the hospital & respective clinic by means of a structured interview with the parents, examination of the patients by otoscopy and by taking info from preceding medical history Results: Comparison was made between180 children having the disease to 150 controls with similar age group who reported in ENT opd & ENT clinics. The calculated six month’s incidence was 180/1000 children 1 to 15 years of age. Meaningfully, increased jeopardy for CSOM was related with a history of acute and recurrent otitis media, a maternal history of COM (chronic otitis media), bigger families and more brethren. The sex, parental age and education, allergy, sinusitis and recurrent URTI were associated with chronic suppurative otitis media. Conclusion: Tympanomastoid surgery is taken into consideration as standard management for CSOMWC, which is unresponsive to oto-topical/oral antimicrobial therapy. Acute and recurrent otitis media, a parental history of chronic otitis media, larger families and more siblings, the sex, parental age and education, allergy, sinusitis and recurrent upper respiratory tract infections are important risk factors for CSOM. In order to improve outcomes, we should modify and cope the controllable risk factors to preclude this life condition.